Answer:
A hot dog would cost 1.75 and the juice would cost 1.05
Step-by-step explanation:
In order to find this, set x as the number of hot dogs and y as the number of juice drinks. This allows us to set up the following equations for each situation.
6x + 4y = 14.70
3x + 4y = 9.45
Now we can mutliply the second equation by -2 to get the x values to cancel out.
6x + 4y = 14.70
-6x - 8y = -18.90
------------------------
-4y = -4.20
y = 1.05
Now that we have this, we can plug it into either equation to find the cost of a hot dog.
3x + 4y = 9.45
3x + 4(1.05) = 9.45
3x + 4.20 = 9.45
3x = 5.25
x = 1.75